Prevalence of depression, anxiety, and associated factors in immigrant pregnant women in Türkiye: A cross-sectional study - Atak, Muhammed; Sezerol, Mehmet Akif; Koçak, Elif Nur; De?er, Mehmet Sait; Kurubal, Hamza (Lippincott Williams and Wilkins, 2023)
The prevalence of depression and anxiety in pregnant women is increasing and this is more important in migrants who are in the vulnerable group. The aim of this study was to evaluate the prevalence of depression and anxiety in Syrian immigrant pregnant women admitted to a Migrant Health Center and the associated factors. The study is a cross-sectional study. A questionnaire prepared using sociodemographic characteristics and the Beck depression and anxiety inventories in Arabic was applied to the participants. The study was conducted with immigrant pregnant women who applied to the Migrant Health Center between July 8, 2022, and December 31, 2022. The study was conducted through health workers who speak Arabic and had received training on the subject beforehand. The mean age of the research group was 26.67?±?5.98 years. Of the participants, 73.0 percent (%) had primary education or less, 95.0% had low income, 87.2% had 3 or less children and 98.5% described their health status as good or very good. The mean Beck anxiety inventory score of the participants was found to be 4.65?±?3.17. The mean Beck depression inventory score was found to be 4.48?±?2.53. Smoking and first pregnancy status were found to be associated with anxiety, whereas smoking and history of delivery beyond 42 weeks were found to be associated with depression (P .05). Anxiety and depression levels of immigrant pregnant women were found to be very low. Minimal anxiety was found in 99.3% of the immigrant pregnant women and 97.1% had no symptoms of depression. It is thought that effective psychosocial support activities for immigrant pregnant women should be carried out in a way to cover the entire target group.
Keywords: Anxiety; Depression; Immigrant; Mental Health; Pregnant